The limits of prudential supervision: Reorganizing the federal bank regulatory agencies - Bernard Shull (Levy Economics Institute of Bard College, 1993)
According to Bernard Shull, although the recent round of banking legislation-most notably the Financial Institutions Reform, Recovery, and Enforcement Act (FIRREA) and the Federal Deposit Insurance Corporation Improvement Act (FDICIA) - did take steps toward preventing financial crises, it did not go far enough in the area of unifying the regulatory structure. Shull proposes unifying federal bank regulatory agencies that presently have flexible authority over competing institutions. In essence, the reorganization would integrate monetary policy and deposit insurance authority with the conventional functions of regulation and supervision. Shull contends that such an integration would foster greater efficiency, improved policy planning, and better accountability while protecting against the hazards of excessive concentration of power. Among the possibilities for a consolidated regulatory agency, Shull prefers consolidation in the Federal Reserve because it is the only banking agency whose structure was originally designed to deal with concerns about concentration of power.
Keywords: 330